Religious Power, the State, Women's Rights, and Family Law. Issue 3 (September 2015) - Htun, Mala; Weldon, S. Laurel
Abstract : Family law is an essential dimension of women's citizenship in the modern state. The rights established in family law shape women's agency and autonomy; they also regulate access to basic resources—such as land, income, and education—that determine a citizen's ability to earn a living independently, among other life chances (Agarwal 1994; Deere and León 2001; Kabeer 1994; Okin 1989; World Bank 2012). Yet family law is a notorious site of sex inequality, historically and in the present. Equal rights enjoyed by women in national constitutions are often contradicted by family and civil codes that subordinate women to the decisions of their husbands and fathers. In the early 21st century, family law in a significant number of countries discriminated against women, denying them the rights held by men and contributing to their disadvantaged social positions.